Prevalence of interpersonal violence against women and men in New Zealand: results of a cross‐sectional study - Janet L. Fanslow; Zarintaj Malihi; Ladan Hashemi; Pauline Gulliver; Tracey McIntosh (Elsevier, 2022)
Abstract Objective: To determine prevalence rates of non‐partner and partner violence (IPV) in men and women from a population‐based study. Methods: We recruited 2,887 randomly selected respondents (1,464 women and 1,423 men) from three regions of New Zealand between 2017 and 2019. Face‐to‐face interviews using a questionnaire adapted from the WHO multi‐country study on violence against women was used for data collection. Results: Physical violence by non‐partners was most commonly experienced by men (39.9% lifetime exposure) compared with 11.9% of women. More women (8.2%) experienced lifetime non‐partner sexual violence compared with men (2.2%). About 29% of men and women reported at least one act of physical‐IPV in their lifetime, and about 12.4% of women and 2.1% of men reported at least one act of lifetime sexual IPV. More women than men reported serious injuries, fear, and physical and mental health impacts following IPV experience. Conclusions: These findings indicate high prevalence of interpersonal violence exposure in the population, with marked gender differences in the types and impacts of violence reported. Implications for public health: Study results call for the urgent implementation of violence prevention programs, and funding for both services to rehabilitate people who have perpetrated violence and services to support recovery of those affected.